1994
DOI: 10.1002/glia.440110203
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic GABA receptors

Abstract: GABA receptors are distributed widely throughout the central nervous system on a variety of cell types. It has become increasingly clear that astrocytes, both in cell culture and tissue slices, express abundant GABAA receptors. In astrocytes, GABA activates Cl(-)-specific channels that are modulated by barbiturates and benzodiazepines; however, the neuronal inverse agonist methyl-4-ethyl-6, 7-dimethoxy-beta-carboline-3-carboxylate enhances the current in a subpopulation of astrocytes. The properties of astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 78 publications
(130 reference statements)
4
61
1
Order By: Relevance
“…Previous studies have shown that substantial amounts of endozepines are spontaneously released by astrocytes (Lamacz et al, 1996) and that glial cells express both GABA A and GABA B receptors (Hösli and Hösli, 1990;Fraser et al, 1994;Bureau et al, 1995). The present data reveal that, at low concentrations (10 Ϫ7 to 10 Ϫ5 M), GABA provokes a dose-dependent inhibition of endozepine release by cultured rat astrocytes.…”
Section: Discussionsupporting
confidence: 45%
“…Previous studies have shown that substantial amounts of endozepines are spontaneously released by astrocytes (Lamacz et al, 1996) and that glial cells express both GABA A and GABA B receptors (Hösli and Hösli, 1990;Fraser et al, 1994;Bureau et al, 1995). The present data reveal that, at low concentrations (10 Ϫ7 to 10 Ϫ5 M), GABA provokes a dose-dependent inhibition of endozepine release by cultured rat astrocytes.…”
Section: Discussionsupporting
confidence: 45%
“…In addition to their classical role as ligand-gated chloride channels of the postsynapse, electrophysiological studies have demonstrated functional expression of GlyR chloride channels (50) and GABA A receptors (51) in astrocytes and other nonsynaptic cells. Due to a lack of synaptic interactions of these cells, ligand-gated ion channels have been proposed to be involved in other functions, such as regulation of cell volume (52), pH (53), and cell proliferation (54).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest the presence of GABA B receptors in astrocytes in vivo (Fraser et al, 1994;Kang et al, 1998;Bekar et al, 1999;Sun and Chiu, 1999;Charles et al, 2003;Queva et al, 2003). With immunohistochemical techniques, this is not easily assessed, because secondary antibodies frequently label glial cells, especially in the white matter.…”
Section: Methodological Considerationsmentioning
confidence: 97%